The Role of Marketing Research in Public Policy Decision Making - Wilkie, William L.; Gardner, David M. (Journal of Marketing, 1974)
GOVERNMENT agencies are making increasingly active attempts to assure and maintain a fair competitive environment for consumers. One important characteristic of these public policy activities has been an underutilization of the skills and insights of researchers in marketing and consumer behavior. This article explores reasons for this underrepresentation and proposes means by which marketing research can contribute to future policy decisions. Although many points made here can apply across government agencies, attention will focus upon the Federal Trade Commission (FTC), where the authors recently completed extensive in-house consulting assignments for the purpose of effecting increased utilization of marketing research by the organization. This experience resulted in several significant conclusions: